Translational Crisis in Biomedical Research: Analysis of Causes and Ways to Overcome It - M. M. Galagudza (Регуляторные исследования и экспертиза лекарственных средств)
The concept of translational gap implies that the intensive development of basic biomedical research at the turn of the 20th and 21st centuries has not, until recently, been accompanied by a proportional increase in the number of innovative drugs, as well as diagnostic and therapeutic technologies that have found application in clinical practice. Mikhail M. Galagudza, Director of the Institute of Experimental Medicine at the Almazov National Medical Research Center of the Russian Ministry of Healthcare, Doctor of Medical Sciences, Professor and Corresponding Member of the Russian Academy of Sciences, shares his thoughts on the causes of the translational crisis and ways of its resolution.